2016
DOI: 10.1080/14786419.2016.1166493
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of 9,10-dihydropyrano[2,3-h]chromene-2,8-dione derivatives in ionic liquid and the study of their antioxidant activity

Abstract: Ionic liquid N,N,N',N'-tetramethylguanidinium trifluoroacetate (TMGT) has been applied as a green and reusable catalyst for the one-pot synthesis of 10-aryl substituted-9,10-dihydropyrano[2,3-h]chromene-2,8-diones via reaction of various aromatic aldehydes, 5,7-dihydroxycoumarin derivatives and Meldrum's acid. The reactions were rapid, clean and the products were prepared in good yield. The ionic liquid was stable during the reaction process and reused without significant loss of its activity. The synthesised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…OMF is a well-known γ-pyrone derivative previously isolated from Talaromyces spp. 25 , 26 , and it was the most abundant secondary metabolite biosynthesized by F36CF in single culture (Fig. 1 , peak at 10.5 min).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…OMF is a well-known γ-pyrone derivative previously isolated from Talaromyces spp. 25 , 26 , and it was the most abundant secondary metabolite biosynthesized by F36CF in single culture (Fig. 1 , peak at 10.5 min).…”
Section: Resultsmentioning
confidence: 93%
“…1 , peak at 10.5 min). OMF exhibited notable antibiotic and antitumor properties 27 , 28 , and recently an insecticidal effect has also been observed 26 , thus expanding the range of its biological activities. Herquline B, earlier purified from a strain of Penicillium herquei , is a nitrogen-containing metabolite acting as platelet anti-aggregation factor 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organosulphur dipeptides in Allium are of special value considering that they are the mediators of its medicinal use and organoleptic characters. Particularly, garlic is enriched in γ-glutamyl peptides and sulfoxides [ 12 ]. The main organosulphur compounds detected in garlic were N -γ-glutamyl- S -allylcysteine, N -γ-glutamyl- S -allylthiocysteine, allithiamine and N -hexosyl- N -γ-glutamyl- S -allylcysteine identified in peaks L6/10, L8/15, L13, and L5.…”
Section: Resultsmentioning
confidence: 99%
“…The study also found that the combination of the essential oil with fluconazole resulted in significant synergistic effects. Vitali et al [ 43 ] demonstrated that the essential oil of Carpathian thymus , which had nerolidol as a major component, presented significant antifungal activities both alone and associated with nystatin. Of note, this is to date, the first study reporting the antifungal properties of liposomal nerolidol.…”
Section: Discussionmentioning
confidence: 99%